Prevent Turtle Trap in the Fishing Gear using Ultrasound - Sunardi, S. (2013)
Malaysian fishing regulation prohibits any fishing activities using gill net since it frequently caused turtles captured in the net. In Malaysia only, the number of turtle landings has been decreasing every year while regulation enforced to prevent turtle extinction had affected fisheries production. Since fishing is an important economic activity especially in east coast and east coast of Peninsular Malaysia, many fishermen still using gill net illegally to gain higher and cheaper production. Plenty of fish had been caught, but turtles trapped in fishing gear are another major problem. It is clear that prohibition is not an effective method. Thus, the proposed research will involve the development of a device based on the findings and integration of previous research. We have found the technical specifications to develop the Turtle Excluder Device that dispels the turtles but enable fish to be caught by gill net. It has successfully determined that turtles are sensitive to specific frequency and signals that can be used to dispel the turtle. In the same time, the transmitted signal does not have any effect to fish.